2014
DOI: 10.1095/biolreprod.114.120899
|View full text |Cite
|
Sign up to set email alerts
|

Soy Promotes Juvenile Granulosa Cell Tumor Development in Mice and in the Human Granulosa Cell Tumor-Derived COV434 Cell Line1

Abstract: Soy attracts attention for its health benefits, such as lowering cholesterol or preventing breast and colon cancer. Soybeans contain isoflavones, which act as phytoestrogens. Even though isoflavones have beneficial health effects, a role for isoflavones in the initiation and progression of diseases including cancer is becoming increasingly recognized. While data from rodent studies suggest that neonatal exposure to genistein (the predominant isoflavone in soy) disrupts normal reproductive function, its role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Two core receptors, BMPR1B and BMPR2, were found to regulate granulosa cell apoptosis in ovaries of humans [45] and sheep [12], respectively. For R-Smads, SMAD1 regulated COV434 cell (a human granulosa cell tumor-derived cell line) apoptosis [46], and SMAD5 suppressed human granulosa cell apoptosis via the FasL-Fas pathway [47,48], but SMAD8 has not been reported to regulate GC apoptosis. Only one Co-SMAD, SMAD4 has been widely demonstrated to be a strong regulator of granulosa cell apoptosis in the ovary of various mammals, such as rodents [46] and pigs [15,17], but not sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two core receptors, BMPR1B and BMPR2, were found to regulate granulosa cell apoptosis in ovaries of humans [45] and sheep [12], respectively. For R-Smads, SMAD1 regulated COV434 cell (a human granulosa cell tumor-derived cell line) apoptosis [46], and SMAD5 suppressed human granulosa cell apoptosis via the FasL-Fas pathway [47,48], but SMAD8 has not been reported to regulate GC apoptosis. Only one Co-SMAD, SMAD4 has been widely demonstrated to be a strong regulator of granulosa cell apoptosis in the ovary of various mammals, such as rodents [46] and pigs [15,17], but not sheep.…”
Section: Discussionmentioning
confidence: 99%
“…For R-Smads, SMAD1 regulated COV434 cell (a human granulosa cell tumor-derived cell line) apoptosis [46], and SMAD5 suppressed human granulosa cell apoptosis via the FasL-Fas pathway [47,48], but SMAD8 has not been reported to regulate GC apoptosis. Only one Co-SMAD, SMAD4 has been widely demonstrated to be a strong regulator of granulosa cell apoptosis in the ovary of various mammals, such as rodents [46] and pigs [15,17], but not sheep. Furthermore, in vivo , both SMAD4 and BMPR1B have been shown to be strongly involved in follicular atresia of domestic animals including sheep [14], pigs [4], and yaks [41].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results also were observed in the incidence of mammary dysplasia in BALB/c mice [ 9 ]. Recently, soy diet has been found to promote granulose cell tumors in C57BL/6 J/129S7/Sv mixed mice [ 33 ]. Although there is genetic variation in physiological sensitivity to E2 between strains of mice, C57BL/6 is one of mouse strains that are highly responsive to E2 [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although many aspects are still unknown, estrogen receptor-mediated effects on cell proliferation contribute to the weight of evidence for estrogen-mediated cancer [ 36 ]. It has been reported that genistein modulates estrogen-receptor expression and signaling in COV434 cells derived from a primary human juvenile granulose cell tumor, promoting cell growth [ 33 ]. In addition, the nature of genetic differences in mouse strains and subspecies is a major source of variation in susceptibility to endocrine disruption by estrogens [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of the FSH receptor was found to inhibit COV434 cell proliferation [147]. Furthermore, incubation of COV434 cells with soy isoflavones, considered to act as phytoestrogens, promoted cell proliferation [148]. Incubation with 5 to 50 μM genistein led to increased expression of ERα and enhanced cell proliferation by repressing proapoptotic genes.…”
Section: Cell-based Systems To Study Effects Of Edcs On Ovarian Steroidogenesismentioning
confidence: 99%